Post-weld heat treatment of GTAW-repaired aluminium 6061-T6 calliper brackets: Effects on surface integrity and micro vickers hardness - Dipo Ariyo Nugroho; Zainal Abadi; Rifelino Rifelino; Andril Arafat (Researcher and Lecturer Society, 2026)
The caliper bracket is a critical component of a motorcycle braking system that maintains the alignment between the brake caliper and the rotor. Repair of damaged caliper brackets is commonly carried out using the Gas Tungsten Arc Welding (GTAW) process. However, the thermal cycle during welding may alter the microstructure and degrade the mechanical properties of Aluminum 6061-T6. To overcome this limitation, post-weld heat treatment (PWHT), in accordance with ASTM B918, can be applied to restore the material properties and enhance the quality of the welded joint. This study investigates the effect of PWHT on the surface quality and microhardness of Aluminum 6061-T6 caliper brackets repaired using the GTAW process. An experimental approach was employed in which all specimens were welded using identical welding parameters and subsequently subjected to PWHT consisting of solution heat treatment, quenching, and artificial aging. Surface quality was evaluated through liquid penetrant testing in accordance with ASTM E165, while microhardness was measured using the Micro Vickers hardness test based on ASTM E384. The penetrant test results revealed that the welded specimens before PWHT contained welding defects, including porosity, lack of fusion, and lack of penetration, with a total of 35 defect indications. After PWHT, the number of defect indications decreased to 19, consisting only of microscopic porosity and lack of fusion. The average microhardness increased from 67.34 HV to 92.26 HV in the Fusion Zone (FZ), from 69.66 HV to 97.78 HV in the Heat-Affected Zone (HAZ), and from 62.44 HV to 95.70 HV in the Base Metal (BM), corresponding to increases of 45.66%, 40.49%, and 53.27%, respectively. Furthermore, PWHT restored the material hardness to 91.62% of the raw material hardness (103.96 HV). These findings demonstrate that PWHT effectively improves both the mechanical performance and the overall quality of GTAW-repaired Aluminum 6061-T6 caliper brackets.